First Blood: Menstrual Regulation and Murderous Rage in Nervous Conditions - Sharma, Ishanika (Research in African literatures, 2025)
This article analyzes how Tsitsi Dangarembga’s 1988 novel Nervous Conditions confounds femininity and fury in its explorations of racism and patriarchy in 1970s Rhodesia. To the extent that it is a story about Tambu seeking education to become upwardly mobile, Nervous Conditions is a cautionary tale about the blunting of her innate sense of justice concerning regimes of race, class, and gender, testing the capacity of the postcolonial Bildungsroman to engage the negativity of feminine anger in the construction of female subjecthood. I discuss a famous but curiously undertheorized fight scene between the female protagonist and her bullying brother to claim that it papers over the rage that propels her trajectory. I examine how the novel provides us with an ambiguous scene of self-determination—one that passes for menarche and attempted murder alike—to grapple with the corrosive force of feminine fury. I read the novel’s figuration of rage in conjunction with how menstrual blood is conceived across religious, cultural, and philosophical discourses. I theorize feminine fury through the negativity that suffuses menstruation.